Sifat Kekonvergenan Lemah pada Ruang Bernorma beserta Operator pada Ruang Barisan Konvergen Lemah - Marabi Djala, Yusuf Betzelial; Ariyanto, Ariyanto; L. Putra, Ganesha; G. Pasangka, Irvandi (Program Studi Matematika Universitas Sulawesi Barat, 2024)
The concept of weak convergence is generated by “weakening” the existing convergence properties in normed spaces. The outcome of this article is to prove the basic properties of weak convergence, the space of weakly convergent sequence is a Banach space and the operators from the space of weakly convergent sequence to other sequence spaces (l1(X),lp(X), linfty(X),S(X) ) and vice versa are linear and bounded .